Characterisation of infectious Ebola virus from the ongoing outbreak to guide response activities in the Democratic Republic of the Congo: a phylogenetic and in vitro analysis. Issue 9 (September 2019) - McMullan, Laura K; Flint, Mike; Chakrabarti, Ayan; Guerrero, Lisa; Lo, Michael K; Porter, Danielle; Nichol, Stuart T; Spiropoulou, Christina F; Albariño, César
Summary: Background: The ongoing Ebola virus outbreak in the Ituri and North Kivu Provinces of the Democratic Republic of the Congo, which began in July, 2018, is the second largest ever recorded. Despite civil unrest, outbreak control measures and the administration of experimental therapies and a vaccine have been initiated. The aim of this study was to test the efficacy of candidate therapies and diagnostic tests with the outbreak strain Ituri Ebola virus. Lacking a virus isolate from this outbreak, a recombinant Ituri Ebola virus was compared with a similarly engineered Makona virus from the 2013–16 outbreak. Methods: Using Ebola virus sequences provided by organisations in DR Congo and a reverse genetics system, we generated an authentic Ebola virus from the ongoing outbreak in Ituri and North Kivu provinces. To relate this virus to other Ebola viruses in DR Congo, we did a phylogenetic analysis of representative complete Ebola virus genome sequences from previous outbreaks. We evaluated experimental therapies being tested in clinical trials in DR Congo, including remdesivir and ZMapp monoclonal antibodies, for their ability to inhibit the growth of infectious Ituri Ebola virus in cell culture. We also tested diagnostic assays for detection of the Ituri Ebola virus sequence. Findings: The phylogenetic analysis of whole-genome sequences from each Ebola virus outbreak suggests there are at least two Ebola virus strains in DR Congo, which have independently crossed into the human population. The Ituri Ebola strain initially grew slower than the Makona strain, yet reached similar mean yields of 3 × 10 7 50% tissue culture infectious dose by 72 h infection in Huh-7 cells. Ituri Ebola virus was similar to Makona in its susceptibility to inhibition by remdesivir and to neutralisation by monoclonal antibodies from ZMapp and other monoclonal antibodies. Remdesivir inhibited Ituri Ebola virus at a 50% effective concentration (EC50 ) of 12nM (with a selectivity index of 303) and Makona Ebola virus at 13nM (with a selectivity index of 279). The Zmapp monoclonal antibodies 2G4 and 4G7 neutralised Ituri Ebola virus with a mean EC50 of 0·24 μg/mL and 0·48 μg/mL, and Makona Ebola virus with a mean EC50 of 0·45 μg/mL and 0·2 μg/mL. The Xpert Ebola and US Centers for Disease Control and Prevention real-time RT-qPCR diagnostic assays detected Ituri and Makona Ebola virus sequences with similar sensitivities and efficiencies, despite primer site binding mismatches in the Ituri Ebola virus. Interpretation: Our findings provide a rationale for the continued testing of investigational therapies, confirm the effectiveness of the diagnostic assays used in the region, and establish a paradigm for the use of reverse genetics to inform response activities in an outbreak. Funding: US Centers for Disease Control and Prevention.